Influence of wall waviness on friction and pressure drop in channels - K. Vajravelu; Ali H. Nayfeh (International Journal of Mathematics and Mathematical Sciences)
An attention has been given to investigate the flow behavior of an incompressible viscous fluid confined in horizontal wavy channels and set in motion due to the movement of the upper wall and the pressure differences. The governing equations have been solved analytically as well as numerically subject to the relevant boundary conditions by assuming that the solution consists of two parts: a mean part and a disturbance or perturbed part. For small and moderate Reynolds numbers, the analytical solution for the perturbed part has been found to be in good agreement with the numerical one. The effects of Reynolds number, the pressure gradient parameter, and the undulation wavenumber on friction and pressure drop are found to be quite significant. In addition to the flow behavior for both long and short waves and for large Reynolds numbers, the effect of the wall waviness on friction and pressure drop has been examined for any arbitrary amplitude of the wavy wall.